Dynamic microparticle manipulation with an electroosmotic flow gradient in low‐frequency alternating current dielectrophoresis. Issue 2 (5th December 2013) - Gencoglu, Aytug; Olney, David; LaLonde, Alexandra; Koppula, Karuna S.; Lapizco‐Encinas, Blanca H.; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> In this study, the potential of low‐frequency AC insulator‐based DEP (iDEP) was explored for the separation of polystyrene microparticles and yeast cells. An EOF gradient was generated by employing an asymmetrical, 20 Hz AC electrical signal in an iDEP device consisting of a microchannel with diamond‐shaped insulating posts. Two types of samples were analyzed, the first sample contained three types of polystyrene particles with different diameters (0.5, 1.0, and 2.0 μm) and the second sample contained two types of polystyrene particles (1.0 and 2 μm) and yeast cells (6.3 μm). This particular scheme uses a tapered AC signal that allows for all particles to be trapped and concentrated at the insulating post array, as the signal becomes asymmetrical (more positive), particles are selectively released. The smallest particles in each sample were released first, since they require greater dielectrophoretic forces to remain trapped. The largest particles in each sample were released last, when the applied signal became cyclical. A dielectropherogram, which is analogous to a chromatogram, was obtained for each sample, demonstrating successful separation of the particles by showing "peaks" of the released particles. These separations were achieved at lower applied potentials than those reported in previous studies that used solely direct current electrical voltages. Additionally, mathematical modeling with COMSOL Multiphysics was carried out to estimate the magnitude of the dielectrophoretic and EOF forces acting on the particles considering the low‐frequency, asymmetrical AC signal used in the experiments. The results demonstrated the potential of low‐frequency AC‐iDEP systems for handling and separating complex mixtures of microparticles and biological cells.